2000
DOI: 10.1016/s0014-5793(00)01224-2
|View full text |Cite
|
Sign up to set email alerts
|

A novel Drosophila serpin that inhibits serine proteases

Abstract: Serpins define a large protein family in which most members function as serine protease inhibitors. Here we report the results of a search for serpins in Drosophila melanogaster that are potentially required for oogenesis or embryogenesis. We cloned and sequenced ovarian cDNAs that encode six distinct proteins having extensive sequence similarity to mammalian serpins, including residues important in the serpin inhibition mechanism. One of these new serpins in recombinant form inactivates, and complexes with, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 24 publications
2
39
0
1
Order By: Relevance
“…Also, SPN55 and SPN48 only formed complexes with the active forms of SAE and SPE, respectively (lanes 7 and 12). Under the same conditions, recombinant Tenebrio SPN1, which shows high sequence identity (37%) with that of Drosophila SPN1 (25) and which was purified as a control serpin, did not form any complexes with the three Toll cascade-activating SPs (lanes 14 -16). These results suggest that the three purified serpins form highly specific serpin⅐protease complexes with the three Toll cascade-activating SPs.…”
Section: Three Purified Serpins Formed Specific Complexes With Threementioning
confidence: 99%
“…Also, SPN55 and SPN48 only formed complexes with the active forms of SAE and SPE, respectively (lanes 7 and 12). Under the same conditions, recombinant Tenebrio SPN1, which shows high sequence identity (37%) with that of Drosophila SPN1 (25) and which was purified as a control serpin, did not form any complexes with the three Toll cascade-activating SPs (lanes 14 -16). These results suggest that the three purified serpins form highly specific serpin⅐protease complexes with the three Toll cascade-activating SPs.…”
Section: Three Purified Serpins Formed Specific Complexes With Threementioning
confidence: 99%
“…The number of functional serpin proteins in Drosophila is likely Ͼ19, because invertebrate serpin genes often have multiple exons that code for reactive centers, allowing for mutually exclusive splicing (Jiang et al, 1994;Kruger et al, 2002). Of particular interest is Spn4, which was reported as one of six serpin-like genes expressed in Drosophila oocytes (Han et al, 2000). Spn4 protein shows significant similarity (30% identity on an amino acid level) to the vertebrate neuronal serpin neuroserpin (Osterwalder et al, 1996;Krueger et al, 1997;Schrimpf et al, 1997).…”
Section: Molecular Analysis Of the Spn4 Genementioning
confidence: 99%
“…Spn4 was initially identified as one of six serpins expressed in Drosophila oocytes (Han et al, 2000) and is the closest Drosophila homolog to neuroserpin, a vertebrate neuronal serpin (Osterwalder et al, 1996;Schrimpf et al, 1997). We analyzed the Spn4 gene and describe two of its alternative splice isoforms, referred to as Spn4.1 and Spn4.2.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary evidence showed that this trypsin-binding protein was a member of the serpin family of antiproteases; purification and sequencing allowed us to identify it as Spn5, a Drosophila serpin first described by Han et al (Han et al, 2000). Spn5 is known to be expressed in the ovary and in embryos and to encode a protein of 427 amino acids, with a predicted signal Northern blot analysis of total RNA isolated from control UAS-Spn5-IR R larvae (oddnumbered lanes), and from Spn5 RNAi expressing larvae carrying the daGal4 driver and the UAS-Spn5-IR R construct (even-numbered lanes).…”
Section: Discussionmentioning
confidence: 99%
“…This band was electroblotted onto a polyvinylidene fluoride (PVDF) membrane and subjected to amino-terminal sequence analysis. The Nterminal sequence of the purified ligand was determined and sequence comparison analysis in the Swiss-Prot data bank revealed that the peptide was identical to a portion of the Drosophila serpin, Spn5, previously identified as a serpin gene with maternal and zygotic expression (Han et al, 2000). The Cterminal region of Spn5 contains highly conserved residues forming the reactive center loop (RCL) with a putative cleavage site for tryptic enzymes as its target proteases.…”
Section: Purification Of the Ligand And Identification As Spn5mentioning
confidence: 98%